Missing the forest for the carbon: Five familiar lessons being learned again in Malaysia - Goh, Chun Sheng *; Gopalasamy, Reuben Clements *; Putz, Francis E. (Malaysia Nature Society, 2023)
As nations scramble to reduce and offset their greenhouse gas emissions to achieve the goals of the Paris Climate Agreement, and corporations do the same for their own reasons, voluntary carbon markets flourish and demand for nature-based carbon credits outpaces supplies. Global attention is on countries with substantial potential to generate certifiable forest-based carbon credits. Despite nearly 30-years of experience with carbon offset projects, forest-based climate change mitigation projects of questionable quality still proliferate in Malaysia and elsewhere. Here, we assess the feasibility and sustainability of the Nature Conservation Agreement (NCA) – a recent project that includes two million hectares of protected forest in the Malaysian state of Sabah. We use this seriously flawed example to identify five key issues that forest carbon projects should not ignore: transparency, additionality, social equity, sovereignty, and complementarity. We also suggest how all five issues could be mitigated by use of a jurisdictional approach to forest carbon project development.